iOS deployment methods in Wisconsin K-12 schools - Fager, Kenneth (My University, 2012)
Wisconsin K-12 school districts are adopting iOS devices (iPad, iPod Touch, iPhone) to address their technology needs. This study examines what general deployment methods are used in conjunction with these devices. Forty-four participants from Wisconsin school districts contributed data through an online survey, and in select cases a follow up interview, that addressed various aspects of iOS device deployment. According to the data the iPad was the most popular iOS device by a nearly 3:1 ratio. Additional findings suggest that school staff is driving deployment, that the devices are being used in Special Education, and that management issues are the most significant difficulty encountered. Recommendations for iOS device deployment in K-12 are provided based on the findings of this study.
This file was last viewed in Adobe Reader X.
Keywords: iPad (Computer); iPod touch (Digital music player); iPhone (Smartphone); Educational technology; Computer-assisted instruction